Pangi Leaf (Pangium edule Reinw) Herbal Medicine: A Marvelous Candidate for the Prominent HIV Herbal Medicine - Arend L Mapanawang; Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
A medicine named as Love herbal (LH) fabricated using zingiberaceae fruit (Golobe halmahera) with a very high concentration ofIC50 = 6.54 ng/ml [1-6] had been compared with pangileaf (Pangium edule Reinw) as well as the combination of pangi-LH herbal medicine especially in their functions of stopping the growth of HIV virus inside T Cell with CD 4 in its surface. By using optical spectroscopy techniques of fast Fourier transform infrared (FTIR), photo cells, and gas chromatography mass spectrometer (GCMS), we found their significant differences. Based on our former finding, the inhibition of pangi leaf was 2.19 times larger than that in love herbal medicine [7]. Such pangi leaf medicine has advantages of optical uniqueness behaviors due to CC at 2260 cm-1 which might be closely in conjunction with very strong alkaline function associated with at least 4 compounds ofoctadecanoic acid (24.6 %), squalene (21.22 %), hexadecanoic acid (15.08 %), and phytol (10.33 %) to kill HIV virus more effectively and safely in human body. The results of our observation under real time photo cells with pure pangileaf medicine at concentration of 400 to 800 ppm were superior to LH medicine. Such output suggests that pangi leaf medicine is very promising for healing HIV patients in the future applications.